2017
DOI: 10.1016/j.ajoc.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A case of congenital retinal macrovessel in an otherwise normal eye

Abstract: PurposeTo present the case of a 37-year-old female with a foveal macrovessel.ObservationsThe patient had an incidental finding of congenital retinal macrovessel (CRM) in the left eye on optical coherence tomography (OCT). Visual acuity was normal, and slit lamp and dilated fundus examinations were otherwise unremarkable. OCT angiography (OCTA) imaging allowed for visualization of the depth profile of the vessel as well as the foveal avascular zone (FAZ). The FAZ and foveal pit were both smaller in the affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Because the majority of sufferers are asymptomatic, congenital retinal macrovessel is usually discovered unexpectedly on physical examinations or in patients with other ophthalmic diseases. In many studies and in normal eyes [6], partial congenital retinal macrovessel can be accompanied by branch retinal artery occlusion [7], retinal deep capillary ischaemia [8], macular retinal cavernous haemangioma [9], retinal arteriolar macroaneurysm [10,11], retinal peripheral telangiectasia [12], vitreous haemorrhage [13], retinal detachment [14], and even venous malformations of the brain [15]. Archer suggested that retinal arteriovenous communications could be divided into three groups [16].…”
Section: Discussionmentioning
confidence: 99%
“…Because the majority of sufferers are asymptomatic, congenital retinal macrovessel is usually discovered unexpectedly on physical examinations or in patients with other ophthalmic diseases. In many studies and in normal eyes [6], partial congenital retinal macrovessel can be accompanied by branch retinal artery occlusion [7], retinal deep capillary ischaemia [8], macular retinal cavernous haemangioma [9], retinal arteriolar macroaneurysm [10,11], retinal peripheral telangiectasia [12], vitreous haemorrhage [13], retinal detachment [14], and even venous malformations of the brain [15]. Archer suggested that retinal arteriovenous communications could be divided into three groups [16].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital retinal macrovessels (CRMs) are aberrant vessels, crossing the horizontal raphe in the macular region and having large tributaries, they are predominantly retinal veins [1,2] originating from the temporal arcade, but could also originate from a retinal artery in 25% of cases or may originate from both arteries and veins. When isolated, CRMs are usually benign and nonvision threatening and most often an incidental finding.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital retinal macrovessels (CRMs) are aberrant vessels typically veins, crossing the horizontal raphe in the macular region that were first described in 1869 [1]. CRMs are usually asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital retinal macrovessel (CRM) is defined as a large aberrant blood vessel that traverses through the central macula. It may have large tributaries extending on both sides of the horizontal raphe 1–3. While it was first described in 1869 by Mauthner, the term CRM was coined in 1982 by Brown et al 1.…”
Section: Introductionmentioning
confidence: 99%